Physical Parameters of Some Flavones - Sinha, K.S.; Kumari, Alka; Rukhaiyar, P.K. (Asian Journal of Chemistry, 2010)
The colour of dye molecules is easily understood with the knowledgeof its electronic structure and its effect on the light absorption in the visibleand near UV region of the spectrum. The Free Electron Molecular Orbial(FEMO) approach is more relevant to the calculation of the spectral characteristicsof dye molecules. The present communication deals with thecalculation of λmax and intensity of absorption band of some flavones.